2022
DOI: 10.1155/2022/3300835
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Elasticity Properties of the Median Nerve during the Upper Limb Neurodynamic Test 1

Abstract: Background. The upper limb neurodynamic test 1 (ULNT1) consists of a series of movements that are thought to detect an increase in neuromechanical sensitivity. In vivo, no trail was made to quantify the association between the nerve elasticity and different limb postures during ULNT1. Objectives. (1) To investigate the relationship between nerve elasticity and limb postures during ULNT1 and (2) to investigate the intra- and interoperator reliabilities of shear wave elastography (SWE) in quantifying the elastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The modified Downs and Black checklist score varied from 9 to 13. Five studies showed good quality (more than 11 points) [49,[52][53][54][55], and 11 showed fair quality (8-11 points) [36,37,50,[56][57][58][59][60][61][62][63]. None of the included studies scored below 9 points.…”
Section: Quality Of the Studiesmentioning
confidence: 94%
See 2 more Smart Citations
“…The modified Downs and Black checklist score varied from 9 to 13. Five studies showed good quality (more than 11 points) [49,[52][53][54][55], and 11 showed fair quality (8-11 points) [36,37,50,[56][57][58][59][60][61][62][63]. None of the included studies scored below 9 points.…”
Section: Quality Of the Studiesmentioning
confidence: 94%
“…The characteristics of the 16 included studies are shown in Tables 2 and 3. In the upper extremity, the median nerve (MN) was assessed in six studies [36,37,55,[61][62][63], while the ulnar nerve (UN) was explored in three studies [37,57,60]. In the lower extremity, the sciatic nerve (SN) and the tibial nerve (TN) were evaluated in six studies [49,50,53,54,58,59] and four studies [36,52,54,56], respectively.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nerve elasticity is a biologically important but understudied concept. This property refers to the ability of nerves to stretch and deform in response to mechanical stress while maintaining their function and structure 1 . Nerve elasticity is particularly important in the peripheral nervous system, where nerves are exposed to a wide range of mechanical stresses and strains as they traverse the body and in the setting of trauma 2 .…”
Section: Introductionmentioning
confidence: 99%
“…This property refers to the ability of nerves to stretch and deform in response to mechanical stress while maintaining their function and structure. 1 Nerve elasticity is particularly important in the peripheral nervous system, where nerves are exposed to a wide range of mechanical stresses and strains as they traverse the body and in the setting of trauma. 2 Nerves’ mechanical properties are also essential for research and development of neural grafts for peripheral nerve regeneration.…”
Section: Introductionmentioning
confidence: 99%